Ansiedade na preparação da performance no ensino de instrumentos de banda - Sousa, Aurélio Nogueira de (2015)
The present text approaches the performance preparation process of the students in the music bands from Goiânia, particularly the impact that anxiety can cause in this process. Since the mid-twentieth century the studies about the preparation for a musical performance with support in other fields such as psychology and neuroscience have intensified. In the reality of the bands, some studies observe that students and teachers need to deal with problems of a psychological nature that interfere in many ways in the teaching-learning process. With the intent of contributing to the advance of these studies, this work aims mainly at detecting what is the impact caused by anxiety in the performance preparation process of the students in the music bands from Goiânia. The methodology has been divided in two main stages. The first was a literature revision about the collective teaching of band instruments and about the musicalization process in the music bands in Brazil. The second was a field research in which the K-MPAI inventory was applied and a specific consultation about performance practice in the music bands from Goiânia has taken place. As the main result of this stage of the research, it was possible to conclude that t level of anxiety in the process of preparation for performance in the students in the 3 music bands investigated from the city of Goiânia is moderate. However, it was detected that some individuals present high levels of anxiety associated with pain, with the lack of information about music psychology as well as unawareness about body maintenance in the musical practice, what indicates that younger musicians are in the need for prevention actions.